Tales from a not-so-fabulous life eaudiobook - Russell, Rachel Renée (Dork Diaries, 2010)
Nikki Maxwell is starting eighth grade at a new school—and her very first diary is packed with hilarious stories and art in this SUPER SQUEE first book in the #1 New York Times bestselling Dork Diaries series! Nikki confesses all in her first diary ever: her epic battle with her mom for an iPhone, meeting her new soon-to-be BFFs Chloe and Zoey, falling for adorably sweet crush Brandon, dealing with her zany little sister Brianna's antics—and the immediate clashes with mean girl MacKenzie, who becomes Nikki's rival in a school-wide art competition. Nearly 30 million books in print worldwide!